Karakterisasi Gejala Klinis pada Kucing dengan Gangguan Gastrointestinal yang Disertai Leukopenia - Ramadhani, Mungky Ema; Yanuartono, Yanuartono -; Indarjulianto, Soedarmanto; Purnamaningsih, Hary; Widyarini, Sitarina; Airin, Claude Mona (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Abstract Gastrointestinal is one of the digestive system disorders in cats that can be characterized by leucopenia. This study aimed to evaluate the clinical symptoms of cats with digestive disorders with leucopenia. This study used 30 cats of various breeds, ages, and genders that had symptoms of digestive disorders with leucopenia. All cats were physically and laboratory examined for hematology. The data obtained were analyzed descriptively. The results showed 18/30 (60%) cats aged 1-6 months, 9/30 (30%) aged 7-12 months, and 3/30 cats (10%) aged >12 months, had gastrointestinal disorders with leucopenia. Leucopenia conditions were more common in male cats (53.3%) than female cats (46.7%). Cats with leucopenia, 10 (33.3%) with a leukocyte count <1,000 cells/mm3, 14 (46.7%) with a leukocyte count of 1,001-2,500 cells/mm3 and 6 (20%) with a leukocyte count of 2,501-<5,500 cells/mm3. Clinical symptoms found in this study included lethargy, anorexia, fever, dehydration, diarrhea, vomiting, halitosis, hypersalivation, anemia, lacrimation, epistaxis and jaundice. Concluded that gastrointestinal disorders with leucopenia were more common in young cats and male cats. Clinical symptoms of lethargy, anorexia, fever, dehydration, diarrhea and vomiting, can be used as a reference to determine the diagnosis of gastrointestinal disorders with leucopenia in cats. Key words: cats; clinical sign; gastrointestinal; leucocytes